FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS IMUNISASI DASAR PADA BAYI DI DESA SUNGAI AIR PUTIH KECAMATAN SUNGAI LALA KABUPATEN INDRAGIRI HULU: Faktor-Faktor yang Mempengaruhi Status Immunisasi Dasar Pada Bayi Di Desa Sungai Air Putih Kecamatan Sungai Lala Kabupaten Indragiri Hilir - Ratna Juwita (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2018)
The immunization program in Indonesia required every infant (0-11 months of age) to receive the complete basic immunization consisting of Hepatitis B, BCG, DPT, Polio and measles. The success of immunization was influenced by several factors such as knowledge, attitude, family support and support of health workers. The Sungai Air Putih Village was the village with the lowest immunization coverage had not reached national target of 91% in 2016 that was (11,1%) with complete basic immunization. This study aimed to determine the factors that affected the status of basic immunization at infants in Sungai Air Putih Village, Sungai Lala District. The type of this research was quantitative with cross sectional approach. The Sampling technique in total sampling, the population in this study was the whole mother who had a baby aged 9-12 months in the River Air Putih village Sungai Lala District. The sample of this study amounted to 34 respondents. The results of this study obtained did not get complete basic immunization as much as 64.7%, 47.1% less knowledgeable mother, 50% of mothers had positive attitudes, 55.9% of families did not support mothers, the low support of health workers as much as 52.9%. The result of chi-square test showed that there was a correlation between knowledge (p = 0,004), attitude (p = 0,012), family support (p = 0,002) and support of health worker (p = 0,006) with basic immunization status in infant. It was expected that the mother to add knowledge about complete basic immunization by following counseling, reading book and browsing on internet. To the health workers to further improve the promotion strategy, to socialize and counseling to mothers who had babies and families, especially about basic immunization to the baby.